ANALISIS YURIDIS PENYALAHGUNAAN KEADAAN (MISBRUIK VAN OMSANDIGHEDEN) SEBAGAI ALASAN PEMBATALAN PERJANJIAN JUAL BELI (STUDI KASUS DALAM PUTUSAN PENGADILAN NEGERI SUKOHARJO NOMOR 19/Pdt.G/2015/PN Skh) - Umarsyah Umarsyah; Pujiyono Pujiyono (Fakultas Hukum Universitas Sebelas Maret, 2026)
This article describes and examines the problems, first, what are the indicators of abuse of circumstances in a sale and purchase agreement. Second, how is the judge's consideration in deciding the sale and purchase agreement which contains elements of acts of abuse of circumstances in the Sukoharjo District Court Decision Number 19/Pdt.G/2015/PN Skh. This article is a normative legal research. The nature of this article is prescriptive using a statutory approach and a conceptual approach. This article uses literature study by collecting primary legal materials and secondary legal materials. The results of data collection were then analyzed using the deductive syllogism method. The results show that the indicators of abuse of circumstances in the sale and purchase agreement are divided into 3 (three) aspects, namely the first in terms of the position of the parties in the contractual phase, the second in terms of the formulation of the agreement, and the third in the aspect of morality. Misuse of conditions in the sale and purchase agreement as a new will has not been clearly regulated in the Civil Code. However, in practice the teaching of abuse of circumstances (misbruik van omstandigheden) contained in the Supreme Court Decision Number 2356 K/Pdt/2008 can be used by judges in the Sukoharjo District Court Decision Number 19/Pdt.G/2015/PN Skh as a reason for canceling the agreement. other than the defects of will that have been regulated in the Indonesian Civil Code, namely coercion (dwang), oversight (dwaling), and fraud (bedrog).